Carbon dioxide utilization: A critical review from multiscale perspective. Issue 12 (28th September 2022) - Yousaf, Muhammad; Zaman, Muhammad; Mahmood, Asif; Imran, Muhammad; Elkamel, Ali; Rizwan, Muhammad; Wilberforce, Tabbi; Riaz, Fahid
Abstract: Carbon dioxide (CO2 ) emissions contribute considerably towards increasing greenhouse effect. Carbon capture and storage can reduce CO2 emissions to a great extent but lacks economic feasibility. The economic feasibility of CO2 capture could be boosted by utilizing the captured gas to produce valuable end products. CO2 is a highly stable molecule; therefore, special catalysts and elevated conditions of temperature and pressure are required for its conversion. This review presents the current status of CO2 utilization processes from various aspects, including thermodynamic, economic, and environmental impacts. The use of process systems engineering (PSE) tools and techniques in a broad spectrum, to improve the technical, economic, and environmental feasibility of these processes, is the major focus of this review. In this regard, a framework has also been presented showing the integration of various PSE techniques. All the related information in the form of tabulated data as well as qualitative and quantitative plots have been presented and critically analyzed. Abstract : This review presents the current status of CO2 utilization processes from various aspects, including thermodynamic, economic, and environmental impacts. The use of process systems engineering (PSE) tools and techniques in a broad spectrum, to improve the technical, economic, and environmental feasibility of these processes, is the major focus of this review. In this regard, a framework has also been presented showing the integration of various PSE techniques. All the related information in the form of tabulated data as well as qualitative and quantitative plots have been presented and critically analyzed.